Research on China's holistic teaching design: Theme evolution, realistic confusion and strategy optimization - Yaqiong Li; Wenbin Xu; Yuchen Pan; Yiwen Xu (Research and Social Study Institute, 2021)
The introduction of subject literacy, the promulgation of